Subcellular Specialization of Mitochondrial Form and Function in Skeletal Muscle Cells - Willingham, T. Bradley; Ajayi, Peter T.; Glancy, Brian (Frontiers in Cell and Developmental Biology, 2021)
Across different cell types and within single cells, mitochondria are heterogeneous in form and function. In skeletal muscle cells, morphologically and functionally distinct subpopulations of mitochondria have been identified, but the mechanisms by which the subcellular specialization of mitochondria contributes to energy homeostasis in working muscles remains unclear. Here, we discuss the current data regarding mitochondrial heterogeneity in skeletal muscle cells and highlight potential new lines of inquiry that have emerged due to advancements in cellular imaging technologies.